ปัญญาประดิษฐ์ในบันเทิงคดีแนววิทยาศาสตร์กับจิตวิญญาณของทศวรรษ 1960 - อรรถพล ปะมะโข (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The objective of this thesis is to study the roles of artificial intelligence characters in science fiction as related to the spirit of the 1960s, which means the pursuit for physical and spiritual freedom to liberate humanity and to create a better society. These roles are influenced by social and cultural changes, including political conflicts between countries, protesting against the Vietnam War, anti-nuclear weapons movement, civil rights movement by second-class citizens of society, and technological advancement which affects human identities.The study reveals that artificial intelligence characters are a significant device used by the authors to reflect and construct the spirit of the 1960s in various aspects. As for the relationship between humans and technology, most artificial intelligence characters are visual representations of various technologies in the 1960s, which provoke human technophobia and cause anxiety in society. However, there are also some artificial intelligence characters that represent the technology leading humanity toward a better society.Artificial intelligence also reveals the idea of both outer and inner freedom. As for the outer freedom, artificial intelligence characters are portrayed in three metaphors. The first metaphor is the "machine as a monster," representing failures of the Establishment. The second is "machine as the Messiah," which is a metaphor for the leader who will liberate humanity from the oppression of the Establishment. The third is "machine as second-class citizens," which shows both ethnic and sexual prejudice in American society. As for the inner freedom, artificial intelligence characters are used as a tool by humans to explore themselves, both in terms of their mental state and identity.Artificial intelligence characters are not only technological concepts that the authors envision to be one element of science fiction, but they also reveal political ideology and spiritual concepts constructed as the spirit of the 1960s.